Enhanced lipid and biomass production by a newly isolated and identified marine microalga. Issue 1 (December 2016) - Dammak, Mouna; Haase, Sandra Mareike; Miladi, Ramzi; Ben Amor, Faten; Barkallah, Mohamed; Gosset, David; Pichon, Chantal; Huchzermeyer, Bernhard; Fendri, Imen; Denis, Michel; Abdelkafi, Slim
Abstract Background The increasing demand for microalgae lipids as an alternative to fish has encouraged researchers to explore oleaginous microalgae for food uses. In this context, optimization of growth and lipid production by the marine oleaginous V2 -strain-microalgae is of great interest as it contains large amounts of mono-unsaturated (MUFAs) and poly-unsaturated fatty acids (PUFAs). Methods In this study, the isolated V2 strain was identified based on 23S rRNA gene. Growth and lipid production conditions were optimized by using the response surface methodology in order to maximize its cell growth and lipid content that was quantified by both flow cytometry and the gravimetric method. The intracellular lipid bodies were detected after staining with Nile red by epifluorescence microscopy. The fatty acid profile of optimal culture conditions was determined by gas chromatography coupled to a flame ionization detector. Results The phenotypic and phylogenetic analyses showed that the strain V2 was affiliated toTetraselmis genus. The marine microalga is known as an interesting oleaginous species according to its high lipid production and its fatty acid composition. The optimization process showed that maximum cell abundance was achieved under the following conditions: pH: 7, salinity: 30 and photosynthetic light intensity (PAR): 133 μmol photons.m−2 .s−1 . In addition, the highest lipid content (49 ± 2.1% dry weight) was obtained at pH: 7, salinity: 37.23 and photosynthetic light intensity (PAR): 188 μmol photons.m−2 .s−1 . The fatty acid profile revealed the presence of 39.2% and 16.1% of total fatty acids of mono-unsaturated fatty acids (MUFAs) and poly-unsaturated fatty acids (PUFAs), respectively.Omega 3 (ω3 ), omega 6 (ω6 ) andomega 9 (ω9 ) represented 5.28%, 8.12% and 32.8% of total fatty acids, respectively. Conclusions This study showed the successful optimization of salinity, light intensity and pH for highest growth, lipid production and a good fatty acid composition, making strain V2 highly suitable for food and nutraceutical applications.